Fluorescence and absorption studies of DNA–Pd(II) complex interaction: Synthesis, spectroanalytical investigations and biological activities. (3rd January 2019) - Thakor, Khyati P.; Lunagariya, Miral V.; Bhatt, Bhupesh S.; Patel, Mohan N.
Abstract: Novel palladium(II) complexes (7a–7e ) of substituted quinoline derivatives were synthesized. The complexes were characterized using various techniques such as thermogravimetric analysis (TGA), elemental analysis, conductance measurement, mass, absorption, infra‐red (IR), 1 H NMR, 13 C NMR and energy‐dispersive X‐ray spectroscopy (EDX). Complexes for herring sperm DNA (HS DNA) binding were explored and absorption titration and the binding constant ( K b ) as well as Gibb's free energy were evaluated. Complex7d exhibited the highest binding constant, therefore the thermodynamic parameters of7d at different temperatures were evaluated. To support the results of the absorption titration, fluorescence titration, viscosity measurement and molecular docking studies were performed. The fluorescence quenching data as evaluated from Stern–Volmer equation were used to calculate K SV, K f and the number of binding sites. The results of all these studies were in good agreement with the absorption study. DNA electrophoretic mobility was performed to explore the possible application of metal complexes as artificial metallonucleases. The antibacterial activity of the complexes was accessed against different pathogenic bacteria and cytotoxicity was measured using brine shrimp and S . pombe .